Interaction of direct and social genetic effects with feeding regime in growing rabbits - Piles, Miriam (Genet Sel Evol, 2017)
BACKGROUND: Most rabbit production farms apply feed restriction at fattening because of its protective effect against digestive diseases that affect growing rabbits. However, it leads to competitive behaviour between cage mates, which is not observed when animals are fed ad libitum. Our aim was to estimate the contribution of direct ([Formula: see text] ) and social ([Formula: see text] ) genetic effects (also known as indirect genetic effects) to total heritable variance of average daily gain ([Formula: see text] ) in rabbits on different feeding regimens (FR), and the magnitude of the interaction between genotype and FR (G × FR). METHODS: A total of 6264 contemporary kits were housed in cages of eight individuals and raised on full ([Formula: see text] ) or restricted ([Formula: see text] ) feeding to 75% of the ad libitum intake. A Bayesian analysis of weekly records of [Formula: see text] (from 32 to 60 days of age) in rabbits on [Formula: see text] and [Formula: see text] was performed with a two-trait model including [Formula: see text] and [Formula: see text] . RESULTS: The ratio between total heritable variance and phenotypic variance ([Formula: see text] ) was low (<0.10) and did not differ significantly between FR. However, the ratio between [Formula: see text] (i.e. variance of [Formula: see text] relative to phenotypic variance) and [Formula: see text] was ~0.52 and 0.86 for animals on [Formula: see text] and [Formula: see text] , respectively, thus [Formula: see text] contributed more to the heritable variance of animals on [Formula: see text] than on [Formula: see text] . Feeding regimen also affected the sign and magnitude of the correlation between [Formula: see text] and [Formula: see text] , i.e. −0.5 and ~0 for animals on [Formula: see text] and [Formula: see text] , respectively. The posterior mean (posterior sd) of the correlation between estimated total breeding values (ETBV) of animals on [Formula: see text] and [Formula: see text] was 0.26 (0.20), indicating very strong G × FR interactions. The correlations between [Formula: see text] and [Formula: see text] in rabbits on [Formula: see text] and [Formula: see text] ranged from −0.47 ([Formula: see text] on [Formula: see text] and [Formula: see text] on [Formula: see text] ) to 0.64. CONCLUSIONS: Our results suggest that selection of rabbits for [Formula: see text] under [Formula: see text] may completely fail to improve [Formula: see text] in rabbits on [Formula: see text] . Social genetic effects contribute substantially to ETBV of rabbits on [Formula: see text] but not on [Formula: see text] . Selection for [Formula: see text] should be performed under production conditions regarding the FR, by accounting for [Formula: see text] if the amount of food is limited.